(untitled) (Research, Society and Development, 2020)
The aim of this study was to analyze the factors that most contributed to pregnancy in the puerperium. It was a descriptive exploratory research with a qualitative approach, which was carried out at the Women’s Health Service in two municipalities in the interior of the State of Rio de Janeiro and at the Integrated Medicine Clinic of a School Hospital, in the obstetrics sector, with a sample of 30 women, where they were interviewed for the collection of data in attention to the proposed objective. The data were analyzed by categorizing responses. Thirty women participated in the research, in the predominant age group 40%, in relation to the number of children 27% reported 04 or more children, about the time interval between pregnancies 50% reported 01 years apart and 67% reported that the pregnancy was not was planned. Three categories of data analysis were created, namely: a) Ineffective communication with puerperal women regarding the prevention of early pregnancy; b) The lack of family planning as an integral part of the puerperal woman’s health care; and c) The lack of dedication in the use of contraceptive methods after pregnancy. It was concluded that according to the study sample, the factors that most influence pregnancy in the puerperium are linked to lack of communication, lack of family planning, which also contributes to the lack of dedication in relation to contraception in the puerperium.